JavaScript for beginners. (Manning Publications, 2022)
Master JavaScript basics and become a JavaScript developer! Whether you want a career in front-end or back-end development, you must have a solid understanding of this universal language. And you are in the right place to learn it, or learn more about it. The course starts from the basics and works up to advanced and expert topics, so it is perfect for both beginners and seasoned JavaScript professionals. It teaches everything you need to get started coding in JavaScript. Highlights include: Comprehensive JavaScript: It's an all-in-one package that will take you from the very fundamentals of JavaScript to building modern and complex applications. Modern JavaScript made easy: You'll receive guidance through fun and practical code examples, critical insights into how JavaScript works behind the scenes, and awesome complete projects. Think like a developer: You'll learn how to plan application features, architect your code, debug code, and many more real-world skills that you will need in your job as a developer. From beginner to expert: Unlike other courses, this one contains beginner, intermediate, advanced, and even expert topics, so you don't have to buy any other course to master JavaScript from the ground up!.